Contributing to the nuclear 3S's via a methodology aiming at enhancing the synergies between nuclear security and safety. (January 2016) - Cipollaro, Antonio; Lomonaco, Guglielmo
Abstract: Nuclear safety, nuclear security and nuclear safeguards regimes have not historically developed at the same pace and surely have not reached the same level of maturity. Nevertheless, these aspects are of special relevance in the current global nuclear energy context when considering the numerous countries that have and will have the legitimate ambition to start a nuclear energy production programme without any or scarce previous nuclear safety, security and safeguards cultures. The future development of nuclear energy exploitation will depend more and more on the convergence of decisions from governments, from the nuclear industry, from utilities, from private and institutional investors as well as from the level of acceptance by the public opinion. Following an in-depth state-of-the-art analysis and literature search, a methodological approach focussed on the safety and security connections is presented, as it seems a field where more commonalities and operational aspects could be possibly found and exploited. Highlights: Nuclear safety, security and safeguards are interactive facets of one same challenge within the nuclear power future context. A methodological approach focussed on the safety and security connections is presented. A paradigm shift in the way nuclear experts are educated and trained is also necessary as they should become able to connect various kind of disciplines.